Protecting rights of asylum seekers and refugees under international law : a case study of the practice of Zambia - Phiri, Shaban Abdul Majeed (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
The world is currently facing unprecedent refugee crisis which has forcibly displaced 65.3 million people world-wide. This has deleterious effect worse than of the First and Second World Wars. Thus, the present refugee crisis has brought untold misery ever witnessed by humanity before. Millions of these refugees are languishing in foreign countries as they are unable to access international protection. Even those that have been granted asylum, their rights and fundamental freedoms are not respected. While millions of others have perished in the waters in their struggle to seek international protection across the Seas and millions of others are internally displaced and persecuted by their own oppressive governments. These are traumatising events which precipitated this research to investigate into the factors responsible for refugee flight, the condition of refugees in countries of asylum and the extent to which international law, the 1951 Refugee Convention and its 1967 Protocol protect the rights and fundamental freedoms of asylum seekers and refugees. A Case Study for this research was conducted in Zambia investigating into its protection system of asylum seekers and refugees, its asylum laws, policies and its implementation of the 1951 Refugee Convention and other international human rights conventions as they constitute part of the Refugee Convention and its Protocol. Thus, this study has established that most violations of human rights of refugees happen the moment they fall into effective control of States of asylum and prior to refugee recognition in form of physical assault, sexual harassments, arbitrary arrests and detention. But this research has proved that every refugee is initially an asylum seeker protected under international law. This research has applied syntheses of doctrinal and non-doctrinal analysis of legal documents, facts and the data qualitatively. Its theoretical framework is predicated on universalism of human rights as inalienable, interrelated and interdependent applicable to every individual human being. Further established that the object and purpose of the Refugee Convention is to ensure that refugees enjoy maximum protection and the rights enumerated in the Convention in the territory of States Parties. It is for this reason that reservations to the Refugee Convention are incompatible with this object and purpose. And further established that human rights conventions including Refugee Convention do not confer on States Parties any reciprocal rights or mutual benefit, but only confer the rights on all individuals in their territory. Another primary focus of this research was on protection system of refugees from Islamic law perspective critically analysed in Chapter Five. This was triggered by the shocking statistics released by the UNHCR that 54 % of the world refugee population is produced from three Muslim States only and, paradoxically, most of these refugees are also hosted by the Muslim States. Further, although Muslim Jurists have not developed Islamic refugee law, this study has established that Islam has long history of refugee protection which predates modern refugee law. By the 6th century, Islam had established all basic principles for the protection of refugees such as the principles of non-refoulement, al-Aman wa al-Musta'amin (safety and protected person), local integration and naturalisation of refugees as a durable solution, the concept of cessation of Hijrah (migration and refugee status), inter alia.